Eksplorasi Seismik Migas sebagai Instrumen Kebijakan Luar Negeri Indonesia: Studi Diplomasi Ekonomi di Wilayah Natuna - Naturrohmah, Aghits (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines how seismic oil and gas exploration in the Natuna region functions as an instrument of Indonesia’s foreign policy within the framework of economic and energy diplomacy. The exploration activities conducted in the strategically significant North Natuna Sea play an important role not only in strengthening national energy security but also in affirming Indonesia’s sovereignty amid the geopolitical dynamics of the South China Sea. This research employs a qualitative document-based case study approach, focusing on the 3D seismic exploration project in the East Natuna Working Area conducted by Pertamina East Natuna (PEN) during 2024–2025. Data were collected through documentary analysis of official government policies, reports from SKK Migas and the Ministry of Energy and Mineral Resources, diplomatic statements, academic publications, and credible international media sources. The data were analyzed using thematic content analysis and process tracing to examine the relationship between energy exploration, economic diplomacy, and foreign policy practices. The findings indicate that seismic exploration in Natuna serves a dual function: as a manifestation of state presence and as a multi-level economic diplomacy instrument operating at the bilateral, regional, and global levels. The activity strengthens Indonesia’s position in international energy forums, attracts foreign investment, and represents a form of soft balancing in response to China’s maritime claims. Therefore, seismic energy exploration in Natuna should not be understood merely as a technical activity, but as an integral component of Indonesia’s energy diplomacy strategy that combines economic interests, foreign policy objectives, and maritime sovereignty.